2022
DOI: 10.3389/fpsyg.2022.856798
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Modus Operandi of Coaches Who Perpetrated Sex Offenses in Canada

Abstract: This study investigated the modus operandi strategies employed by 120 coaches who committed sexual abuse toward 331 athletes under their authority. More than 2,000 Canadian court judgements and media reports were identified using online search databases. Using descriptive analysis, 51 strategies used in six modus operandi stages were identified. Results highlighted the most frequent strategies used by coaches for each stage of the crime commission process. Additionally, findings revealed the influence of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
(109 reference statements)
0
0
0
Order By: Relevance
“…At first glance, it seems notable that the effect sizes for observed sexual violence are slightly stronger than those for experienced sexual violence-especially for peer violence. However, at second glance, this difference, although not previously hypothesized makes sense; studies on perpetrator strategies have revealed that, in general, perpetrators pick their victims deliberately, concentrating on those athletes who seem to be receptible or vulnerable (St-Pierre et al 2022). Thus, not everyone in a sport group is "eligible" as a victim, and these individual characteristics exist independently of the empowering climate within the group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…At first glance, it seems notable that the effect sizes for observed sexual violence are slightly stronger than those for experienced sexual violence-especially for peer violence. However, at second glance, this difference, although not previously hypothesized makes sense; studies on perpetrator strategies have revealed that, in general, perpetrators pick their victims deliberately, concentrating on those athletes who seem to be receptible or vulnerable (St-Pierre et al 2022). Thus, not everyone in a sport group is "eligible" as a victim, and these individual characteristics exist independently of the empowering climate within the group.…”
Section: Discussionmentioning
confidence: 96%
“…For all other factors, the effects were similar, no matter whether the context is observed sexual violence, experienced sexual violence in general, or sexual violence by the coach. One explanation for this effect may be that perpetrators of sexual violence use trust-building strategies to groom potential victims (St-Pierre et al 2022), and these strategies can be seen as socially supportive by athletes. Thus, social support might not be a decisive subfactor within an empowering and disempowering climate when it comes to sexual violence.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, athletes become dependent on the coach (e.g., their sports performance), and this can be misused to eventually achieve their goal: sexual violence [68,69]. St-Pierre et al [70] studied the modus operandi of coaches who perpetrated sex offences in Canada: half of them had an authoritarian coaching style that made athletes feel intimidated. Behaviours, such as negative feedback, directive communication and focus on performance as the only goal are typical for this coaching style [71].…”
Section: Powermentioning
confidence: 99%